Drabbl Genre in Uzbek and Russian Literature: On the Example of the Works of Anton Chekhov and Abdulla Qahhor (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes the artistic and aesthetic features of the drabble as a distinct form of short prose in Russian and Uzbek literature. Through a comparative analysis of Anton Chekhov’s and Abdulla Qahhor’s literary heritage, the study reveals the formation, development, and literary-aesthetic potential of short story genres. The research extensively discusses the depth of content, brevity of form, and literary significance of the drabble genre, highlighting both similarities and differences between the two authors’ works.